Diabetic kidney disease: from pathogenesis to multimodal therapy–current evidence and future directions - Zhang, Hui; Wang, Keding; Zhao, Hairui; Qin, Bowen; Cai, Xiaojing; Wu, Manyi; Li, Junhua; Wang, Jielian (Frontiers in Medicine, 2025)
Diabetic kidney disease (DKD) has emerged as the leading cause of chronic kidney disease (CKD) worldwide, surpassing primary glomerular disorders in prevalence. Despite recent therapeutic advances, current treatment strategies primarily alleviate symptoms rather than address the underlying pathogenic mechanisms, highlighting an urgent need for targeted, mechanism-based interventions. The pathogenesis of DKD involves a complex interplay of metabolic, hemodynamic, inflammatory, oxidative, and fibrotic pathways. Chronic hyperglycemia initiates a cascade of molecular events—including the accumulation of advanced glycation end products (AGEs), activation of the polyol pathway, enhanced protein kinase C (PKC) signaling, and mitochondrial dysfunction—culminating in glomerular hyperfiltration, podocyte injury, and progressive glomerular and tubulointerstitial fibrosis. In addition to these classical mechanisms, emerging processes such as ferroptosis (iron-dependent cell death), impaired autophagy, gut microbiota dysbiosis, and epigenetic alterations offer promising therapeutic targets. Current DKD management integrates lifestyle modifications with four cornerstone pharmacologic classes: renin–angiotensin–aldosterone system inhibitors (RAASi), sodium–glucose co-transporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP-1 RAs), and mineralocorticoid receptor antagonists (MRAs). Notably, evidence from clinical trials suggests that simultaneous modulation of multiple pathogenic pathways provides superior cardiorenal protection compared to monotherapy. Investigational therapies—including endothelin receptor antagonists (ERAs), nuclear factor erythroid 2–related factor 2 (Nrf2) activators, and gut microbiota modulators—are under active evaluation. Additionally, Traditional Chinese Medicine (TCM) formulations have demonstrated albuminuria-lowering effects in clinical studies. Future research should prioritize biomarker-driven precision medicine approaches, enabling individualized therapy selection and development of agents that concurrently target ferroptosis and inflammation. Given the multifaceted pathophysiology of DKD, optimal management will require multimodal, patient-tailored regimens that address hyperglycemia, hypertension, inflammation, and fibrosis to effectively slow or halt disease progression.